Mechanisms for upward migration of methane in marine sediments - Liu, Haotian; Zhan, Linsen; Lu, Hailong (Frontiers in Marine Science, 2022)
Methane, a non-negligible component of the global carbon budget, could be discharged upward through marine sediments to ocean floor by certain migration mechanisms. Although quite some studies have been conducted, the mechanisms for methane migration have not been well reviewed yet, especially in hydrate-bearing sediments. In this study, methane migration mechanisms are classified into diffusion and advection processes which include water movement, free gas flow, sediment failures, and recently developed gas migration through hydrate channels. The occurrence of natural gas hydrate might affect methane migration in three ways: (1) reducing the permeability of marine sediments and consequently hindering the upward movement of methane either in gas or liquid phase, (2) enhancing the geomechanical strength of marine sediments, which prevents the creation of new pathways for methane escape by sediment failure, and (3) benefiting upward methane migration by constructing hydrate channels at the interface of continuous gas columns. Generally, dissolved methane could hardly break through the gas hydrate stability zone and sulfate-methane transition zone because of the high consumption rate for methane in these two zones. For free methane gas, the capillary force is a strong resistance to free gas flow in porous sediments. However, whether for dissolved methane or free methane gas, discharge along pre-existing fractures or failure surfaces might be considerable. In addition, methane discharge by gas flow through hydrate channels is still hard to constrain. Finally, based on current research uncertainties in constraining the methane flux to the ocean, the research outlook is also addressed. It is suggested that more investigations should be conducted in three aspects: the flow characteristic of high-permeability conduits, the quantitative correlations of geomechanical properties and hydrate distribution, and the occurrence conditions of hydrate channels.